An analysis of the relationship between corporate carbon disclosure and financial performance: a study of companies listed in the FTSE/JSE responsible investing index - Mathebula, Andzani George (My University, 2023)
The international nature of the climate change challenge complicates the cost analysis. Researchers have therefore concluded that atmospheric carbon concentrations influence climate change, and that greenhouse gas emissions may be a contributing factor, leading policy makers in several countries to examine options for reducing emissions of greenhouse gases, particularly carbon dioxide (CO2). There are at least four ways to estimate the "cost of carbon emission reductions: (1) the carbon tax necessary, which measures the marginal cost of the final tonne of emissions cut; (2) the total direct cost, which measures the marginal cost of all emissions reductions; (3) the loss in GDP." A wide range of businesses' economic performance and behaviour are directly impacted by carbon emissions. “This study was aimed at examining, using quantitative methods, the relationship between Corporate Carbon Disclosure and Financial Performance of the top 30 companies listed in the FTSE (Financial Times Stock Exchange) and JSE (Johannesburg Stock Exchange) Responsible Investing Index. The study results showed that sales revenue is negatively correlated to carbon disclosure, although the relationship is statistically insignificant. The regression results showed that the relationship between Carbon Disclosure and Return on Equity is statistically insignificant implying independence between the variables, despite the negative correlation being established”. The study results also showed that Earnings per Share is negatively correlated to Carbon Disclosure, although the relationship was not statistically significant. The study recommends the crafting of comprehensive Carbon Disclosure metrics, which enable objective measurement of the variable and establishment of the statistically significant relationship with performance measures and the improvement in stakeholder involvement and engagement in order to improve the level of carbon disclosure and financial performance. Legislations should be made in order to compel all organisation listed on the JSE to disclose the impact of their operations on the environment. The study also recommends that organisations diversify their activities to include environmentally friendly operations. Green activities improve the image of the firm in the market which leads to improvement in the financial activities. In addition, diversification to green activities motivates the organisation to engage more on carbon disclosure
Thesis (MBA.) -- University of Limpopo, 2023
Keywords: Corporate Carbon Disclosure; Financial Performance; Companies; Emissions trading; Financial institutions -- Management; Business enterprises -- Finance; Stock exchanges